Thoo Thoo - Qasri, Qaiser (Department of Languages and Cultures of Asia, UW-Madison, 2008)
Translation of Qaiser Qasri's short story "Thu Thu" from the collection Vatan ka Qarz.
Keywords: Urdu literature; Urdu short stories; Urdu literature